2019
DOI: 10.1136/bmjopen-2018-023586
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for diabetic retinopathy in a cross-sectional population-based study from rural southern China: Dongguan Eye Study

Abstract: Research questionThe current population-based study aimed to investigate the prevalence of diabetic retinopathy (DR) and risk factors among residents over 40 years old in the rural area of Dongguan, southern China.Study designThe Dongguan Eye Study was a population-based study from September 2011 to February 2012.SettingThe area was set in the rural area of Dongguan, southern China.ParticipantsAdult rural population aged 40 or older.InterventionParticipants underwent haematological, physical, ophthalmic examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 32 publications
(74 reference statements)
9
42
4
Order By: Relevance
“…Diabetic retinopathy more commonly occurs in elderly individuals with diabetes. In our study, it was revealed that the mean age of patients with type diabetes was 51.3 years and the mean age of patients with type 2 diabetes was 63.8 years, which are quite similar to other studies (9,10). Regarding gender, the number of female patients (58.4%) was slightly more than males in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Diabetic retinopathy more commonly occurs in elderly individuals with diabetes. In our study, it was revealed that the mean age of patients with type diabetes was 51.3 years and the mean age of patients with type 2 diabetes was 63.8 years, which are quite similar to other studies (9,10). Regarding gender, the number of female patients (58.4%) was slightly more than males in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Association of poor glycemic control with diabetic retinopathy was also shown by studies done in other parts of the world. 21,[28][29][30][31] This difference in the ndings between our study and other studies may have resulted from the use of HbA1c to assess level of glycemic control in the studies mentioned.…”
Section: Discussionmentioning
confidence: 72%
“…In the response to stress especially in DLP, the inflammatory mediators are upregulated leading to abnormal leucocyte-endothelial interactions and eventually retinal microvascular damage [ 6 , 28 , 29 ]. However, a cross-sectional study in southern China reported no association was found between cholesterol levels and DR [ 30 ].…”
Section: Discussionmentioning
confidence: 99%